Nitrous oxide emissions from grazing cattle urine patches: Bridging the gap between measurement and stakeholder requirements. (January 2016) - Cook, F.J.; Kelliher, F.M.
Abstract: Nitrous oxide (N2 O) is a potent greenhouse gas and a precursor to compounds which deplete stratospheric ozone. Agricultural soils are the principal anthropogenic N2 O source, which includes urine patches of cattle fed by grazing pasture. While such N2 O emissions can be measured, involved time and space scales are usually only minutes and metres, respectively. Nevertheless, climate change stakeholders need large-scale national emissions over time to construct annual N2 O emissions inventories for international treaty compliance requirements. We have developed a mathematical model to bridge the gap between measurement and stakeholder requirements for N2 O emissions from grazing cattle urine patches. Our methodology begins with the emissions from a patch. Convolution integrals are then used to spatially and temporally scale the emissions from discrete grazing events to paddock, farm and region levels across the year. The model developed shows how the emissions are smoothed out with scaling and the implications from the scaling. Graphical abstract: a) Flux of N2 O with time when parameters change with season during the milking season. Milking (grazing) starts on 14th of July continues for 48 days with the winter response parameters. On 1st of September, 1st January, 1st of March and 1st June the response parameters change to the values for Spring, Summer, Autumn and winter respectively. The milking season finishes on 20th June and urine patch generation is taken to cease as the cows are removed from the farm. The farm area, herd size and urination rate are given in Table 2. b) The flux if the seasonal response function parameters were used for the whole annual cycle. Highlights: A model that scales nitrous oxide (N2 O) emissions from urine patches in space and time is developed. The time to develop a residual flux density is estimated to take less than one year and decay will take 3–5 half-lives. Results show that a small difference occurs with the present emission factor method and this difference is able to be computed. The model is most sensitive to patch scale parameters and the area covered by urine patches. Variation of the response function parameters during the annual cycle can impact on the annual flux density.